Serum TNFRII: A promising biomarker for predicting the risk of subcentimetre lung adenocarcinoma. Issue 7 (19th February 2020) - Hu, Minjuan; Zhang, Yanwei; Sun, Beibei; Lou, Yuqing; Zhang, Xueyan; Wang, Huimin; Huang, Chengya; Zhang, Wei; Chu, Tianqing; Han, Baohui
Abstract: Early diagnosis of lung adenocarcinoma requires effective risk predictors. TNFRII was reported to be related to tumorigenesis, but remained unclear in lung cancer. This research set out to investigate the relationship between the sTNFRII (serum TNFRII) level and the risk of lung adenocarcinoma less than 1 cm in diameter. Seventy‐one pairs of subcentimetre lung adenocarcinoma patients and healthy controls were analysed through multiplex bead‐based Luminex assay and found a significantly lower expression of sTNFRII in patients with subcentimetre lung adenocarcinoma than that in the healthy controls ( P  < .001), which was further verified through ONCOMINE database analysis. Increased levels of sTNFRII reduced the risk of subcentimetre lung adenocarcinoma by 89% ( P  < .001). Patients with a higher level of BLC had a 2.70‐fold ( P  < .01) higher risk of subcentimetre adenocarcinoma. Furthermore, a higher BLC/TNFRII ratio was related to a 35‐fold higher risk of subcentimetre adenocarcinoma. TNFRII showed good specificity, sensitivity and accuracy (0.72, 0.75 and 0.73, respectively), with an AUC of 0.73 ( P  < .001). In conclusion, the present study assessed the value of sTNFRII as a potential biomarker to predict the risk of subcentimetre lung adenocarcinoma and provided evidence for the further use of TNFRII as an auxiliary marker in the diagnosis of subcentimetre lung adenocarcinoma.